2019
DOI: 10.1098/rsbl.2019.0185
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D : 4D) and prosocial behaviour in economic games: no direct correlation with generosity, bargaining or trust-related behaviours

Abstract: Prenatal exposure to sex hormones exerts organizational effects on the brain which have observable behavioural correlates in adult life. There are reasons to expect that social behaviours—fundamental for the evolutionary success of humans—might be related to biological factors such as prenatal sex hormone exposure. Nevertheless, the existing literature is inconclusive as to whether and how prenatal exposure to testosterone and oestrogen, proxied by the second-to-fourth digit ratio (2D : 4D), may predict non-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…Whilst similar correlations have been found previously [see, e.g., Brañas-Garza et al. (2019)], our correlation appears to be on the low side (e.g., Neyse et al. (2016) find correlations of 0.727 for men and 0.765 for women), however, other studies also find even lower correlations (e.g., Bönte et al.…”
supporting
confidence: 88%
“…Whilst similar correlations have been found previously [see, e.g., Brañas-Garza et al. (2019)], our correlation appears to be on the low side (e.g., Neyse et al. (2016) find correlations of 0.727 for men and 0.765 for women), however, other studies also find even lower correlations (e.g., Bönte et al.…”
supporting
confidence: 88%
“…Considering the fact that not only our, but also other studies do not support the hypothesis that the digit ratios are related to testosterone levels 28 , or even prenatal hormones 8,63,64 (but see also 65 ), it may seem surprising that the abundant body of literature provides evidence for the links between the 2D:4D and many adult characteristics, such as aggressiveness 66 , personality traits 30 , or substance and computer use 29 . What may seem even more confusing, is that some other, recent studies have reported the 2D:4D to be a non-significant predictor of other traits and behaviors, for instance: risk or pro-social behaviors 67,68 , risk taking 69 , grip strength 70 . One of the possible explanations of such discrepancies may be taking into account a size of an individual.…”
Section: Discussionmentioning
confidence: 98%
“…First, we note that the relationship between testosterone exposure and social preferences appears complex. Whereas Buser (2012) and Cecchi and Duchoslav (2018) report that public good game contributions are lower for L DR types (in line with the hypothesis that high-testosterone types are less cooperative), Brañas-Garza et al (2013) and Galizzi and Nieboer (2015) find that dictator game giving is significantly lower for those with H and L DR, compared to those with average DR. Brañas-Garza et al (2019) find no direct correlation between DR and dictator game giving, fairness or trust. In contrast, studies on risk taking present a more harmonious set of findings.…”
Section: Dr and Competitive Behaviormentioning
confidence: 64%